Pelaksanaan Suntik Tetanus Toxoid (TT) Peraturan Walikota Binjai Nomor 39 Tahun 2017 Sebagai Syarat Administrasi Pernikahan Di Kua Binjai Barat (Kajian Fiqh Munakahat Dalam Pemahaman Imam Syafi’i) - Lubis, Salsabila (Jurnal Landraad, 2024)
This study examines the implementation of the Tetanus Toxoid (TT) injection as a requirement for marriage administration based on the Mayor of Binjai Regulation No. 39 of 2017, focusing on the perspective of fiqh munakahat and Imam al-Shafi'i’s understanding. The regulation aims to ensure the health of prospective spouses and prevent disease transmission, especially for mothers and their future children. However, the application of this requirement raises questions regarding its relevance within the framework of Islamic law and fiqh. This research employs a qualitative method with a normative and juridical approach. Data were collected through interviews, observations, and literature review. The findings indicate that, from the fiqh munakahat perspective, the TT injection as an administrative requirement does not contradict Islamic principles as long as it serves the purpose of maslahah (well-being) and harm prevention. According to Imam al-Shafi’i’s understanding, actions that bring benefit and prevent harm are aligned with the objectives of maqasid al-shariah. Therefore, this policy can be considered compatible with Islamic values, provided it does not act as an absolute barrier to the marriage process.